2012
DOI: 10.1589/jpts.24.1263
|View full text |Cite
|
Sign up to set email alerts
|

What Can Be Achieved by Mutual-understanding among Community-dwelling Elderly People and Physical Therapy Students?

Abstract: Abstract.[Purpose] The purpose was to clarify how community-based classes affected students, community staff, and elderly people.[Methods] Students collaborated in exercise classes for community-dwelling elderly people (participants) with teachers and community staff. After classes, questionnaires were completed by 60 participants, 9 community staff, and 24 students. Questionnaires consisted of a five-grade evaluation, a visual analogue scale (VAS), and impressions described in freely written sentences. All se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The community capacity code was given to articles that measured how much intergenerational programs impacted a community's ability to provide services or raise funds to support individuals in the community. A total of 14 (6.45%) articles cited community outcomes focused on capacity building, including reports on overall capacity and community development (Gallagher & Fitzpatrick, 2018; Weinronk et al, 2017), revenue (Hwang et al, 2014), public safety (Yasunaga et al, 2016), and education (e.g., Doiron & Lees, 2009; Nakagawa & Asakawa, 2012). Specifically, intergenerational programs can increase understanding across the community, which can enhance a community's social capital, leading to greater levels of safety felt within the community (Yasunaga et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The community capacity code was given to articles that measured how much intergenerational programs impacted a community's ability to provide services or raise funds to support individuals in the community. A total of 14 (6.45%) articles cited community outcomes focused on capacity building, including reports on overall capacity and community development (Gallagher & Fitzpatrick, 2018; Weinronk et al, 2017), revenue (Hwang et al, 2014), public safety (Yasunaga et al, 2016), and education (e.g., Doiron & Lees, 2009; Nakagawa & Asakawa, 2012). Specifically, intergenerational programs can increase understanding across the community, which can enhance a community's social capital, leading to greater levels of safety felt within the community (Yasunaga et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Articles reporting how intergenerational programs affect the number and quality of resources available to the wider community were coded in this category. Eight articles (3.69%) reported that intergenerational programs impacted local community resources including, information systems (Foret et al, 1998; Nakagawa & Asakawa, 2012), transportation and errand assistance (Blake, 1986; Pynoos et al, 1984), mentorship (e.g., Doiron & Lees, 2009; Henkin & Rodriguez, 2018), and home-based health services (Pynoos et al, 1984). The connections built within an intergenerational program can open additional channels of communication between individuals and organizations across a community, leading to improved information dissemination and systems that serve as an additional resource to the rest of the community (Foret et al, 1998; Nakagawa & Asakawa, 2012).…”
Section: Resultsmentioning
confidence: 99%